Akses dan Perlindungan Informasi Koleksi Digital Pada Layanan Repository Universitas Muhammadiyah Pontianak - Sahidi (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Institutional repository as a media that specifically manages local content information in digital form belonging to institutions that can provide benefits for the Muhammadiyah University of Pontianak library. The purpose of this study is to describe access and information protection strategies for digital collections and to describe providing user access to information on the library repository service at the Muhammadiyah University of Pontianak. The research method used in this research is a case study with a descriptive analysis of a qualitative approach. Data collection techniques using interviews, observation, and documentation. The results of this study indicate that the Pontianak Muhammadiyah University Library has not implemented an open information access policy for users of the institution's repository collection. All collections in the form of final projects in the repository are only limited to the beginning and the final chapter which can be accessed and downloaded in full text. As for the digital collection security strategy; First, not all of the digital collections stored in the repository can be downloaded in full text and can only be read (read only), secondly, to secure the digital collection on the IR itself, it is locked using several applications, thirdly, to work with IT so that the server is available. always stable and able to control and secure digital collections.